Modulation of the activity of N-methyl-D-aspartate receptors as a novel treatment option for depression: current clinical evidence and therapeutic potential of rapastinel (GLYX-13) - Vasilescu, Andrei-Nicolae; Gass, Peter; Inta, Dragos (Neuropsychiatric disease and treatment, 2017)
Modulation of the activity of N-methyl-D-aspartate receptors as a novel treatment option for depression: current clinical evidence and therapeutic potential of rapastinel (GLYX-13) Andrei-Nicolae Vasilescu,1,* Nina Schweinfurth,2,* Stefan Borgwardt,2,* Peter Gass,1 Undine E Lang,2,* Dragos Inta,1,2,* Sarah Eckart2,* 1Department of Psychiatry and Psychotherapy, Central Institute of Mental Health, Medical Faculty Mannheim, Heidelberg University, Heidelberg, Germany; 2Department of Psychiatry (UniversitÃ¤re Psychiatrische Kliniken), University of Basel, Basel, Switzerland *These authors contributed equally to this work Abstract: Classical monoaminergic antidepressants show several disadvantages, such as protracted onset of therapeutic action. Conversely, the fast and sustained antidepressant effect of the N-methyl-d-aspartate receptor (NMDAR) antagonist ketamine raises vast interest in understanding the role of the glutamate system in mood disorders. Indeed, numerous data support the existence of glutamatergic dysfunction in major depressive disorder (MDD). Drawback to this short-latency therapy is its side effect profile, especially the psychotomimetic action, which seriously hampers the common and widespread clinical use of ketamine. Therefore, there is a substantial need for alternative glutamatergic antidepressants with milder side effects. In this article, we review evidence that implicates NMDARs in the prospective treatment of MDD with focus on rapastinel (formerly known as GLYX-13), a novel synthetic NMDAR modulator with fast antidepressant effect, which acts by enhancing NMDAR function as opposed to blocking it. We summarize and discuss current clinical and animal studies regarding the therapeutic potential of rapastinel not only in MDD but also in other psychiatric disorders, such as obsessivea-compulsive disorder and posttraumatic stress disorder. Additionally, we discuss current data concerning the molecular mechanisms underlying the antidepressant effect of rapastinel, highlighting common aspects as well as differences to ketamine. In 2016, rapastinel received the Breakthrough Therapy designation for the treatment of MDD from the US Food and Drug Administration, representing one of the most promising alternative antidepressants under current investigation. Keywords: depression, glutamate, NMDARs, rapastinel, ketamine